47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1360
|View full text |Cite
|
Sign up to set email alerts
|

Recent Enhancements to the FUN3D Flow Solver for Moving-Mesh Applications

Abstract: An unsteady Reynolds-averaged Navier-Stokes solver for unstructured grids has been extended to handle general mesh movement involving rigid, deforming, and overset meshes. Mesh deformation is achieved through analogy to elastic media by solving the linear elasticity equations. A general method for specifying the motion of moving bodies within the mesh has been implemented that allows for inherited motion through parent-child relationships, enabling simulations involving multiple moving bodies. Several example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 24 publications
0
98
0
Order By: Relevance
“…First introduced by Thomas and Lombard [19], it has been shown mathematically and through numerical experiment [20][21][22] that satisfying the GCL can improve the accuracy and stability of the chosen scheme. A straightforward technique for the numerical implementation of the GCL [23,24] has been included as part of the dual-time stepping approach.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…First introduced by Thomas and Lombard [19], it has been shown mathematically and through numerical experiment [20][21][22] that satisfying the GCL can improve the accuracy and stability of the chosen scheme. A straightforward technique for the numerical implementation of the GCL [23,24] has been included as part of the dual-time stepping approach.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…25 The mesh deformation is accomplished by treating the mesh motion as analogous to a linear elasticity problem. 26 The linear elasticity equations are written in finite-volume form and evaluated in a manner similar to the integration of the conservation form of the flow equations.…”
Section: Methods Of Analysis a Fun3d Aeroelastic Solvermentioning
confidence: 99%
“…This value has been chosen based on numerical experience and represents a compromise between temporal accuracy and computational cost. Ideally, an error-based subiterative controller such as that described in [6] would be used; such an approach is available for the solution of (2.4), but has not been implemented for (3.4). The effect of time step size was investigated and it was found that the asymptotic mean value of the lift coefficient did not change significantly using more than 100 steps per blowing cycle.…”
Section: Baseline Conditions and Aerodynamic Performancementioning
confidence: 99%
“…The mesh is modeled as an elastic medium that obeys the elasticity relations of solid mechanics, where an auxiliary system of linear partial differential equations (PDEs) is solved to determine the mesh coordinates after each shape update. Discretization of these PDEs yields a linear system of equations: 6) where K represents the elasticity coefficient matrix and X is the vector of updated surface coordinates, complemented by zeros for all interior coordinates. Thus for the static grid formulation used here, the grid operator takes the specific form:…”
Section: Grid Equationsmentioning
confidence: 99%
See 1 more Smart Citation